Grammatical Errors in Writing Recount Texts Committed by the Tenth Grade Students of Madrasah Aliyah (MA) Thohir Yasin Lendang Nangka in the School Year of 2015/2016 - ZAENUL FIKRI (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2020)
This study was meant to discover the types of grammatical errors commited by the tenth graderof students in writing recount texts, and to discover why those errors happen. This study was acase study with qualitative approach. The subject of this study was 51 students of the tenthgrader of Madrasah AliyahThohirYasinLendangNangka in the School Year of 2016/2017. Theinstrument used in this study was written test of recount text. Data collection method used inthis study was observation, interview, and documentation. The data was analyzed by classifyingthe types of grammatical error into seven categories and then determined the possible causesof those errors according to the theory of Erdogan(2005). The result showed that: (1) Thestudents made 323 grammatical errors in 431 sentences classified into 98 or 30.3% errors inproducing verb groups, 112or 34.7% errors in subject-verb agreement, 46 or 14.2% errors inpluralization, 18 or 5.6% errors in the use of article, 20 or 6.2% errors in the use of preposition,12or 3.7% errors in the use of pronoun, and 17or 5.3% errors in the use of conjunction.(2) Thepossible causes of those errors are: intra-lingual transfer (88%) and inter-lingual transfer (12%).Key words: Grammatical Errors, Recount Text.ABSTRAKPenelitian ini bertujuan untuk menemukan jenis-jenis grammatical errors yang dibuat oleh siswakelas X di dalam menulis recount text, dan untuk menemukan penyebab errors tersebut.Penelitian ini merupakan studi kasus dengan menggunakan pendekatan qualitative. Subjekpenelitian ini sebanyak 51 siswa kelas X Madrasah Aliyah Thohir Yasin Lendang Nangka Th.Pelajaran 2016/2017. Instrument yang digunakan adalah tes tulis dalam bentuk recount text.Metode pengumpulan data yang dipakai dalam penelitian ini adalah observasi, interview, dandokumentasi. Data dianalisis dengan mengklasifikasikan jenis-jenis grammatical errors dankemudian menentukan kemungkinan penyebab errors tersebut dengan mengacu kepada teoriErdogan (2005). Hasil yang didapatkan adalah: (1) siswa membuat 323 grammatical errors dari431 kalimat dengan klasifikasi sebagai berikut: 98 atau 30,3 % errors di dalam membuat verbgroups, 112 atau 34,7 % errors pada subject-verb agreement, 46 atau 14,2 % errors padapluralization, 18 atau 5,6 % errors pada penggunaan article, 20 atau 6,2 % errors padapenggunaan preposistion, 12 atau 3,7 % errors pada penggunaan pronoun, dan 17 atau 5,3 %errors pada penggunaan conjunction. (2) kemungkinan penyebab errors tersebut adalah: intralingualtransfer (88%) dan inter-lingual transfer (12%)Kata Kunci: Grammatical Errors, Recount Text